2007
DOI: 10.1007/s10461-006-9191-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Religious Congregation Members’ Support to People Living with HIV/AIDS in Kumasi, Ghana

Abstract: Physical, social and economic constraints often limit the ability of people living with HIV/AIDS to meet their basic needs. Community members are a valuable source of support for people living with HIV/AIDS, although little is known about the types of support they provide or how to mobilize this support. To examine this issue, a survey of 1200 members of 6 religious congregations was conducted in Kumasi, Ghana. A fifth of congregation members reported providing some support to people with HIV/AIDS in the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Research in Ghana indicated that hearing a leader speak about HIV/AIDS had a substantial effect on congregants’ provision of support to people with HIV (Bazant & Boulay, 2007). Studies elsewhere (e.g., Jamaica, Trinidad, Tanzania, Uganda, Tanzania, Malawi) have found that FBOs can move from fostering to dissuading stigma through trainings that increase knowledge and understanding of HIV among clergy and congregations members, increased personal contact between congregational leaders and people with HIV, creating social spaces that are supportive to people with HIV, and direct involvement of people with HIV in congregational prevention, care and advocacy efforts (Campbell et al, 2010; Genrich & Brathwaite, 2005; Hartwig et al, 2006; Muturi, 2008; Otolok-Tanga et al, 2007; Trinitapoli, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in Ghana indicated that hearing a leader speak about HIV/AIDS had a substantial effect on congregants’ provision of support to people with HIV (Bazant & Boulay, 2007). Studies elsewhere (e.g., Jamaica, Trinidad, Tanzania, Uganda, Tanzania, Malawi) have found that FBOs can move from fostering to dissuading stigma through trainings that increase knowledge and understanding of HIV among clergy and congregations members, increased personal contact between congregational leaders and people with HIV, creating social spaces that are supportive to people with HIV, and direct involvement of people with HIV in congregational prevention, care and advocacy efforts (Campbell et al, 2010; Genrich & Brathwaite, 2005; Hartwig et al, 2006; Muturi, 2008; Otolok-Tanga et al, 2007; Trinitapoli, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, FBOs have been proposed as institutions that could be critical to the community response to HIV. FBOs have served as venues, participants, and organizers of HIV testing (Whiters et al, 2010), housing for HIV positive individuals (Derose, Dominguez et al, 2010), prevention education (Agate et al, 2005; Berkley-Patton et al, 2010; Griffith et al, 2010; Lindley et al, 2010), and food, social support, pastoral care, and other services for people living with HIV (Derose et al, 2011; Bazant & Boulay, 2007; Leong, 2006). And studies of FBO efforts across multiple countries have found that care and support activities are considered traditional strengths of FBOs, even though HIV prevention efforts have been highly contested within religious circles, often disrupting collaborative efforts (Parker & Birdsall, 2005; Tiendrebeogo & Buykx, 2004; Woldehanna et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that promising avenues for engaging congregations in the response to HIV are through their leaders, especially by increasing personal contact between congregational leaders and people with HIV. Research in Ghana found that hearing a leader speak about HIV had a substantial effect on congregants’ provision of support to people with HIV [61]. Studies elsewhere (e.g., Jamaica, Trinidad, Tanzania, Uganda) have found that faith-based organizations can move from fostering to dissuading stigma through trainings that increase knowledge and understanding of HIV among clergy and congregation members and increase personal contact between congregational leaders and people with HIV [62–65].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to relying on prayer, these women frequently consult their religious leaders for advice and support as they make decisions about disclosing their status to family and community members. Similarly, Bazant and Boulay (2007) show that religious congregations in Ghana are an important source of material and social support for people living with HIV and AIDS, and that having heard about AIDS from religious leaders positively predicts the provision of such support.…”
Section: Introductionmentioning
confidence: 96%
“…In other words, this study develops an articulation of what religious leaders are doing about AIDS, and what motivates them to take a hands-on approach to addressing the epidemic in their communities. Though I focus exclusively on the role of religious leaders in prevention messages, I acknowledge that the scope of this paper does not encompass the roles of religious leaders who, along with their congregations, are relevant to other aspects of the AIDS epidemic, like disclosure (Maman et al 2009), treatment, and caregiving (Agadjanian and Menjivar 2008, Bazant and Boulay 2007). …”
Section: Introductionmentioning
confidence: 99%